ESTIMULAÇÃO INDIVIDUAL DO DESENVOLVIMENTO NEUROPSICOMOTOR EM UMA CRIANÇA: RELATO DE CASO - Llano, Débora C.; Pretto, Luciana M.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo